Analysis of Ability To Pay & Willingness To Pay BPJS Health Contribution Among Informal Sector Workers in Indonesia - Ferdhitya Rizky Syauqi; Ratno Adrianto (Mulawarman International Conference on Tropical Public Health, 2025)
Background : BPJS Kesehatan is Indonesia’s national health financing scheme supporting equitable access to healthcare and the achievement of Universal Health Coverage. However, premium payment compliance among informal sector workers remains low due to unstable income, high basic household expenditures, and limited financial security. This condition creates a persistent gap between Ability to Pay (ATP) and Willingness to Pay (WTP). Beyond economic constraints, perceived service benefits, service quality, and health insurance literacy significantly influence WTP. Considering the large proportion of informal workers in the national labor market, understanding ATP and WTP determinants is essential for designing adaptive and sustainable financing policies. Objective : To analyze factors influencing ATP and WTP for BPJS Kesehatan premiums among informal sector workers in Indonesia through a systematic review of national literature published from 2020–2025, and to identify policy implications for strengthening long-term financing sustainability. Research Methods / Implementation Methods : A Systematic Literature Review (SLR) was conducted using national SINTA-indexed journals and Indonesian scientific databases. Keywords related to “Ability to Pay BPJS,” “Willingness to Pay BPJS,” and “Informal Sector Workers” were used. Inclusion criteria covered quantitative Indonesian-language studies (2020–2025) examining ATP/WTP in the context of BPJS Kesehatan. Fourteen articles met the criteria and were thematically analyzed based on economic factors, socio-demographic characteristics, household expenditure patterns, and perceived health service quality. Results : Findings show that ATP is mainly shaped by unstable income, high basic household expenditures, and fluctuating informal earnings. These structural characteristics make consistent premium payments difficult and indicate that a uniform flat-rate contribution is incompatible with the economic realities of informal workers.WTP, meanwhile, is strongly influenced by perceived benefits, service experience, information access, and trust in healthcare services. Higher WTP is observed when workers perceive real value and understand the long-term advantages of BPJS participation. Low health insurance literacy and lack of perceived service quality reduce willingness to pay.The review highlights the need for flexible premium schemes tailored to informal economic segments, such as micro-installment models, and emphasizes that improving WTP also requires better communication, transparency, and service quality. Conclusion / Lesson Learned : ATP among informal workers is dominated by economic constraints, while WTP is shaped by perceived benefits and service trust. Sustainable BPJS financing requires flexible, segmented premium models and parallel improvements in service quality. Future policies should integrate both economic and perception-based strategies to enhance compliance and reduce premium arrears.